Medical ethics in residency training - (:unkn) unknown (TURKISH SOC CARDIOLOGY, 2009)
Medical ethics education in residency training is one of the hot topics of continuous medical education debates. Its importance and necessity is constantly stressed in declarations and statements on national and international level. Parallel to the major structural changes in the organization and the finance model of health care system, patient-physician relationship, identity of physicianship, social perception and status of profession are changing. Besides, scientific developments and technological advancements create possibilities that never exists before, and bring new ethical dilemmas along with. To be able to transplant human organs has created two major problems for instance; procurement of organs in sufficient numbers, and allocating them to the patients in need by using some prioritizing criteria. All those new and challenging questions force the health care workers to find authentic and justifiable solutions while keeping the basic professional values. In that sense, proper medical ethics education in undergraduate and postgraduate term that would make physician-to-be's and student-physicians acquire the core professional values and skill to notice, analyze and develop justifiable solutions to ethical problems is paramount. This article aims to express the importance of medical ethics education in residency training, and to propose major topics and educational methods to be implemented into. To this aim, first, undergraduate medical education, physician's working conditions, the exam of selection for residency training, and educational environment were revised, and then, some topics and educational methods, which are oriented to educate physicians regarding the professional values that they should have, were proposed. (Anadolu Kardiyol Derg 2009, 9: 132-8)
Keywords: Residency; professional education; graduate medical education; medical ethics; bioethics; professional ethics; PROFESSIONALISM; EDUCATION; ENVIRONMENT; BIOETHICS; PROGRAMS; NEEDS